ATP Binding Cassette Transporter Mediates Both Heme and Pesticide Detoxification in Tick Midgut Cells - Lara, Flavio Alves (2015)
In ticks, the digestion of blood occurs intracellularly and proteolytic digestion of hemoglobin takes place in a dedicated type of lysosome, the digest vesicle, followed by transfer of the heme moiety of hemoglobin to a specialized organelle that accumulates large heme aggregates, called hemosomes. In the present work, we studied the uptake of fluorescent metalloporphyrins, used as heme analogs, and amitraz, one of the most regularly used acaricides to control cattle tick infestations, by Rhipicephalus (Boophilus) microplus midgut cells. Both compounds were taken up by midgut cells in vitro and accumulated inside the hemosomes. Transport of both molecules was sensitive to cyclosporine A (CsA), a wellknown inhibitor of ATP binding cassette (ABC) transporters. Rhodamine 123, a fluorescent probe that is also a recognized ABC substrate, was similarly directed to the hemosome in a CsA-sensitive manner. Using an antibody against conserved domain of PgP-1-type ABC transporter, we were able to immunolocalize PgP-1 in the digest vesicle membranes. Comparison between two R. microplus strains that were resistant and susceptible to amitraz revealed that the resistant strain detoxified both amitraz and Sn-Pp IX more efficiently than the susceptible strain, a process that was also sensitive to CsA. A transcript containing an ABC transporter signature exhibited 2.5-fold increased expression in the amitraz-resistant strain when compared with the susceptible strain. RNAi-induced down-regulation of this ABC transporter led to the accumulation of metalloporphyrin in the digestive vacuole, interrupting heme traffic to the hemosome. This evidence further confirms that this transcript codes for a heme transporter. This is the first report of heme transport in a blood-feeding organism. While the primary physiological function of the hemosome is to detoxify heme and attenuate its toxicity, we suggest that the use of this acaricide detoxification pathway by ticks may represent a new molecular mechanism of resistance to pesticides.